Conceptualizing, Investigating, and Enhancing Adaptive Expertise in Elementary Mathematics Education - Verschaffel, Lieven; Luwel, Koen; Torbeyns, Joke; Van Dooren, Wim (European Journal of Psychology of Education, 2009)
Some years ago, Hatano differentiated between routine and adaptive expertise and made a strong plea for the development and implementation of learning environments that aim at the latter type of expertise and not just the former. In this contribution we reflect on one aspect of adaptivity, namely the adaptive use of solution strategies in elementary school arithmetic. In the first part of this article we give some conceptual and methodological reflections on the adaptivity issue. More specifically, we critically review definitions and operationalisations of strategy adaptivity that only take into account task and subject characteristics and we argue for a concept and an approach that also involve the sociocultural context. The second part comprises some educational considerations with respect to the questions why, when, for whom, and how to strive for adaptive expertise in elementary mathematics education. (Contains 9 notes.)
Keywords: résolution de problèmes